COVID-19 in Patients With Rheumatic Diseases: Is There a Need to Worry?. Issue 2 (26th March 2022) - Sachdeva, Sonali; Manaktala, Pritika; Malik, Faizan Ahmad; Gupta, Udita; Desai, Rupak
Abstract : Background/Objectives: SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), first described in December 2019, has infected more than 33 million people and claimed more than 1 million deaths worldwide. Rheumatic diseases are chronic inflammatory diseases, the prevalence and impact of which in COVID-19 patients are poorly known. We performed a pooled analysis of published data intending to summarize clinical presentation and patient outcomes in those with established rheumatic disease diagnosis and concurrent COVID-19. Methods: PubMed and Google Scholar were searched to identify studies reporting data about rheumatic disease patients who were diagnosed with SARS-CoV-2 infection and published until July 22, 2020. Random-effects models were used to estimate the pooled incidence and rates of hospitalization, intensive care unit admission, and mortality among these patients, and interstudy heterogeneity was identified using I 2 statistics with greater than 75% value indicating substantial interstudy variation. Results: Twenty studies were included, giving a total sample size of 49, 099 patients positive for SARS-CoV-2. Of 49, 099 COVID-19 patients, a total of 1382 were also diagnosed with a rheumatic disease in the past. The random-effects pooled prevalence of COVID-19 among rheumatic disease patients was found to be 0.9%. The rates of hospitalization, intensive care unit admission, and mortality were 70.7%, 11.6%, and 10.2%, respectively. Conclusions: Although the prevalence of SARS-CoV-2 infection is not dramatically high in rheumatic disease patients, concurrent COVID-19 does seem to play a role in determining disease severity and outcomes to some extent. Further studies are needed to give conclusive evidence about whether this subset of the population is at a higher risk of COVID-19 and related outcomes compared with the population at large.